Penerapan Metode Brainstorming pada Pembelajaran Fisika Materi Wujud Zat - Sunandar, Dwi; Effendi, Effendi (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2018)
Innovation in a learning is an important factor in determining the success of the learning process of learners. Therefore, teachers should be able to choose and determine either a strategy, method or even a learning approach in accordance with learning materials and learning objectives. The use of methods or appropriate learning techniques on a learning material will support the effectiveness of the process in it. The purpose of this study was to determine the influence of brainstorming techniques on student physics learning outcomes on learning material form Substance. This research is a quantitative research. Technique of collecting data (was) using test. Moreover, research hypothesis was tested using t-test formula. Based on the results of data analysis obtained, the average score on the experimental class is 81.66 while that on control class is 71.00. Hypothesis testing which obtains tcount = 4,595 with price t table = 2,000, indicates that the price of t arithmetic is not in the acceptance area of H0. H0 is rejected because the acceptance area is between - ttable = - 2,000 to ttable = 2,000 for 60 of degree of freedom with significance level 5%. Therefore, Ha is accepted. It means that there is significant impact of brainstorming toward students achievement on learning state of matter.